2015
DOI: 10.1182/blood-2014-07-590232
|View full text |Cite
|
Sign up to set email alerts
|

Lung parenchyma-derived IL-6 promotes IL-17A–dependent acute lung injury after allogeneic stem cell transplantation

Abstract: Key Points IL-6 is dysregulated after experimental allogeneic SCT and promotes alloantigen-dependent Th17 expansion within the lung. IL-6 is dysregulated in patients with IPS after clinical allogeneic SCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 42 publications
2
88
0
2
Order By: Relevance
“…Using an allo-SCT-induced model of lung injury, we have previously demonstrated the importance of IL-6 in driving Th17 development. 2 Here, we also observed Th17 differentiation to be highly dependent upon IL-6R signaling in all tissues examined ( Figure 1C). IL-17A expression was transient such that the proportion of CD4…”
Section: Yfpmentioning
confidence: 56%
See 3 more Smart Citations
“…Using an allo-SCT-induced model of lung injury, we have previously demonstrated the importance of IL-6 in driving Th17 development. 2 Here, we also observed Th17 differentiation to be highly dependent upon IL-6R signaling in all tissues examined ( Figure 1C). IL-17A expression was transient such that the proportion of CD4…”
Section: Yfpmentioning
confidence: 56%
“…Although calcineurin inhibition is known to have broad immunosuppressive effects on T-cell responses, including a significant reduction in overall Th17 frequencies, 2 we found that CsA treatment successfully reduced the transition of IL-17A 1 IFNg -Th17 toward an IFNg2producing phenotype ( Figure 4A-B). Because we have previously demonstrated that donor antigen-presenting cells (APCs) are a major source of IL-12 posttransplant, 37 we examined the effect of CsA using IL-12p40-YFP reporter mice.…”
Section: Relative Expressionmentioning
confidence: 76%
See 2 more Smart Citations
“…Cutaneous pathology also may be generated by Th17 cells; although they are more commonly associated with chronic GVHD (cGVHD), they also have been associated with acute pathology (22)(23)(24). Th17 differentiation is initiated by IL-6 (25), and RORgt is the defining transcription factor (26), whereas maintenance and amplification relies on IL-23 and IL-21, respectively (27).…”
Section: Cytokines and Acute Gvhdmentioning
confidence: 99%